PENGARUH FASILITAS DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT HONDA ALEXSANDER BERSAUDARA DI KOTA BATAM - Frisca, Anita; Afridola, Sri (SCIENTIA JOURNAL, 2019)
The development of business ventures is increasingly marked by the increasing level competition between companies and the existence of business opportunities in motorcycle services that make many entrepreneurs interested in opening the business. The purpose study was to determine the effect of facilities and services on customer satisfaction where the independent variable is Facility and Service, affecting customer satisfaction as the dependent variable.The population used study is customer service service customers and the purchase of PT Honda Alexsander motorcycle spare parts in Batam, sample of 100 respondents used as PT Honda Alexsander customers in Batam.The sampling collection method uses the Slovin method and the data collection technique uses a questionnaire. This type of research is quantitative research. Quantitative analysis includes validity, reliability, classic assumption test, multiple linear analysis, coefficient of determination (R2), f test and t test. Data from study were processed using SPSS version 20. The results study are that the facilities partially have a positive and significant influence on purchasing decisions, service has a positive and significant effect on purchasing decisions. While simultaneous results, facilities and services have a significant influence on customer satisfaction at PT Honda Alexsander in the city of Batam.